O direito dos desastres e sua interface com a improbidade administrativa dos agentes públicos - Vieira, Paulo Eduardo de Almeida (Universidade do Vale do Rio dos Sinos, 2020)
Faced with an unprecedented civilization and environmental crisis, producing a singular state of deterioration of the planet, the Law, as a normative social subsystem, is expected to stimulate a paradigmatic review capable of presenting efficient responses that confront the abundant, contingent and plural risks, capable, at least in potential, of triggering a definitive collapse of humanity. This desirable change of standards cannot be made possible without a reformulation of perspectives, much less without overcoming absolute anthropocentrism as a standard of rationality. As a goal, it will not be achieved if the due importance of autophagic consumption, everything that it drags out and the expressive degradation that comes from it, is evaded. There is also an unforgivable misunderstanding about the central role of disasters as the most tangible by-product of this world in crisis and of an unsustainable environmental modernity. For this reason, the gravity of the extreme event, whether natural, anthropogenic or even mixed, must be fixed, either because of its astonishing speed or even because of its indefinite extension, as well as because of the significant mutations it produces at the social-moral-economic levels, in order to make it emerge that state intervention cannot be suppressed or shortened for the construction of another sustainable rationality. In this scenario, Disaster Law is called upon to contribute with a different normative style, opening alternatives for the improvement of the axes of prevention, mitigation, response and compensation to disasters, without paralyzing life in society. Its task is Herculean, since it calls for a profound change in the rationality of the State, in conditions to bring about other ways of thinking and inhabiting the world, organized by an environmental ethic of intergenerational equity and the consolidation of the idea of the environment as a fundamental human right. The change of perspective and orientation presupposes that Disaster Law, in its specificity, is capable of dialogue with the traditional matrices of the legal system itself and overcome them to some extent, in order to demarcate and consolidate its epistemic territory. Thus, it can conform, with its legal rationality, the instruments of environmental governance, green or grey infrastructures and the evaluation of ecosystem services. The legal instruments foreseen in the National Environmental Policy should be emphasized, resignifying them in order to account for the mentioned risks and dangers, especially if associated with the monitoring and contingency plans that make up the National Civil Defense Policy. Disaster Law also invites the development of a new deconstruction program, when it rescues the role of civil liability, in order to focus not only on the damage caused, but especially on the future. The State, in contrast, propitiates the emergence of the collection of the resumption of its role of relevant environmental action to confront these events of magnitude, focusing on the necessary and adequate exercise of police power, from its reconfiguration as an affirmative action of environmental law. Finally, as a hypothesis, on the condition of contributing to mitigate failures by undue action or omission of the State, directly or indirectly related to extreme events, it revives and gives consistency to the legal protection of the action of administrative improbity, as a mechanism for deterring disasters and their repetition. Finally, overcoming the inertia of mere warnings and the description of dangers and risks of late modernity, to assume the central role of confronting the multiple causes of disastrous events. The research strategy adopted was explanatory and propositional, the nature of the qualitative approach and the method used was deductive.
Keywords: Desastres; Crise ambiental; Ética ambiental; Responsabilidade civil do Estado; Improbidade administrativa; Disaster; Environmental crisis; Environmental ethics; State civil liability; Administrative improbity; ACCNPQ::Ciências Sociais Aplicadas::Direito